Unpacking the link between adaptive capacity, assets and responses of rural livelihoods facing multiple stressors in the Eastern Cape - Dalu, Mwazvita Tapiwa Beatrice (Rhodes University, Faculty of Science, Department of Environmental Science, 2020)
Southern Africa has been plagued by multiple interacting shocks and stressors in the past decades, which have rendered this region even more socially vulnerable, which in turn affects their adaptive capacity. The continuing perpetual state of lack of assets, compounded by high sensitivity to climate change driven shocks and stressors, such as food insecurity, therefore, leaves many households' livelihoods vulnerable. Thus, there is a need to identify ways to implement adaptation initiatives; or to find means to improve the adaptive capacity of rural households and communities in Southern Africa, including those in the Eastern Cape Province of South Africa. However, despite recent work in other parts of the world regarding adaptive capacity, our understanding of adaptive capacity and adaptive needs in specific regions or communities is still limited. Furthermore, heterogeneity (inter- and intra-households), is often not accounted for in many studies, limiting our understanding on how differentiated household compositions affect and/or are affected by assets, agency and capabilities; and how this impacts upon adaptive capacity and responses of these households. Thus, greater attention needs to be paid to the social inequalities of vulnerability amidst multiple stressors. This study therefore explored; i) variations in vulnerability across heterogeneous household characteristics as influenced and reflected by assets and responses both at the single household and community levels; ii) how household and community level assets and responses interacted with institutions and organisations at various scales (as barriers and enablers (toadaptive responses which affect adaptive capacity)), and; Page ii iii) how pre-existing vulnerabilities in heterogeneous households influenced current adaptive capacities and how institutions and organisations influence current and future adaptive capacity. In addition to the conceptual framework used in this research, structural transformations, asset functions and multiple stressors, the Local Adaptive Capacity and the Sustainable Livelihood Frameworks were also considered. The main findings of this research showed a considerable prevalence of liquid asset poverty in rural households in the Eastern Cape, being more pronounced in female-headed households, households with an elderly head and in small sized households. Livestock were found to be the dominant asset type. However, as land management is under communal arrangement, issues of power, access and control need to be considered with respect to how they can better accommodate vulnerable societal groups. Findings revealed a prevalence of erosive coping strategies at the household levels. Collective responses were also found to be greatly affected by a lack of knowledge and conflicts, whilst also displaying exclusionary tendencies towards women. Overall, the adaptive capacity of households in the study area showed a need for better policy and contextspecific intervention in education, equal rights and opportunity creation.
Keywords: Climatic changes; Adaptive capacity; Kat River Valley (South Africa); Multiple stressors; Sustainable livelihood; Vulnerability; Asset